2011
DOI: 10.2147/nss.s18897
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in Parkinson's disease patients and management options

Abstract: Sleep disturbances are among the most common nonmotor complaints of patients with Parkinson’s disease (PD), and can have a great impact on quality of life. These disturbances manifest in a variety of ways; for instance, insomnia, sleep fragmentation, and excessive daytime sleepiness. Sleep-related movement disorders such as restless legs syndrome and periodic leg movements may share a common pathophysiology, and occurrence of rapid eye movement behavior disorder may predate the onset of PD or other synucleinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 100 publications
0
38
0
Order By: Relevance
“…219 Non-motor symptoms of PD, including disturbances in sleep and mood, can emerge years before the motor symptoms. 136,220,221 In particular, individuals in the early stages may present with depression or anxiety that may be more distressing or interfering than the motor symptoms. 222 Accordingly, exercise programs are particularly well suited to early implementation in PD with the potential for diffuse non-motor benefits (e.g.…”
Section: Treatment Stage and Exercise Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…219 Non-motor symptoms of PD, including disturbances in sleep and mood, can emerge years before the motor symptoms. 136,220,221 In particular, individuals in the early stages may present with depression or anxiety that may be more distressing or interfering than the motor symptoms. 222 Accordingly, exercise programs are particularly well suited to early implementation in PD with the potential for diffuse non-motor benefits (e.g.…”
Section: Treatment Stage and Exercise Interventionmentioning
confidence: 99%
“…[126][127][128][129] Sleep disruptions are common among older adults 130 and are particularly problematic and multifactorial in PD, 40,131,132 with reference to this problem dating to James Parkinson's observations in his original essay. 133 Fragmented sleep has been reported, [134][135][136][137][138][139] attributed in part to nighttime motor symptoms, 140,141 with reports of sleep benefits upon control of these symptoms. 142,143 Individuals with PD may present with REM sleep behavior disorder, excessive daytime sleepiness, and sleep-onset and sleepmaintenance insomnia, as well as sleep disordered breathing, restless leg syndrome, and nocturia.…”
Section: Sleep Disruption In Pdmentioning
confidence: 99%
“…Insomnia is known as a sleep disturbance in PD patients as well as a side effect of medication [28]. Brunner et al reported that dopaminergic medication including levodopa and cabergoline increased the number of awakening and duration of stage 1 sleep, by comparing between pre-medication and post-medication in the de novo PD patients [29].…”
Section: Association Between Anti-pd Drugs and Incidence Of Insomnia mentioning
confidence: 99%
“…The PD‐specific sleep‐related symptoms include sleep fragmentation, sleep initiation difficulties, excessive daytime sleepiness (EDS), restless leg syndrome and rapid eye movement behaviour disorder (Crabb, ). Of these, the most common and disabling sleep symptom is sleep fragmentation, which is defined as the interruption of the sleep stages resulting in either a stage of lighter sleep or awakening that affects the normal sleep structure (Claassen & Kutscher, ). Collectively, these sleep‐related problems cause fatigue, morning headaches, and cognitive and mood disturbances including depression, which may lead to a loss of productivity, work‐related accidents and withdrawal from social activities (Buttaro, Trybulski, Polgar‐Bailey, & Sandberg‐Cook, ).…”
Section: Introductionmentioning
confidence: 99%